Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Kooperatif Tipe Scramble Pada Siswa Kelas III Sekolah Dasar - Aisyah Fitri; Tin Indrawati (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by the lack of optimal integrated thematic learning that involves students not understanding the material so that it has an impact on learning outcomes. This purpose of this research is to describe the Improvement of Integrated Thematic Learning Outcomes Using Cooperative Models of Scramble Type in Class III Students of SD Kartika 1-11 Padang. The type of research is PTK with qualitative and quantitative. The research data is in the form of research and test results. The study was conducted in two cycles. The research subjects were teachers and students class III. The results of the study in terms of lesson plan I cycle 84.72%, cycle II 92%. The activity of teacher and student cycle I 80.4% (B), cycle II 92.9% category (SB). Student Cycle I Aspects Reflecting the Mutual Cooperation Attitude and Not Reflecting the Attitude of Independence Intelligence, cycle II students reflect the attitude of mutual cooperation, integration and independence. Knowledge aspect of cycle I is 2.66 (B), cycle II is 3.66 category (SB). Skill aspect of cycle I is 3.00 (B), cycle II is 4 categories (SB). Keywords: scramble type cooperative model, Enhancement, integrated thematic learning.